2021
DOI: 10.3390/jcm11010130
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Microvascular Vasodilatory Function: Related Clinical Features and Differences According to the Different Coronary Arteries and Types of Coronary Spasm

Abstract: Background: In the clinical setting; the microvascular vasodilatory function test (MVFT) with a pressure wire has been used in ischaemia patients with non-obstructive coronary arteries (INOCA), including vasospastic angina (VSA) and microvascular angina (MVA). The exact factors that affect the microvascular vasodilatory function (MVF) in such patients are still unknown. We aimed to identify the factors, including clinical parameters and lesion characteristics, affecting the MVF in such patients. Methods: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…Taken together, these findings suggest that unstable atherosclerotic lesions may be present at the focal spastic sites. Recently, it was reported that coronary microvascular dysfunction may contribute to INOCA[ 28 ], and such coronary microvascular dysfunction was more frequently observed in coronary arteries with focal spasm than in those with diffuse spasm[ 22 ]. Such coexistence of coronary microvascular dysfunction may, in part, contribute to readmission for UAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings suggest that unstable atherosclerotic lesions may be present at the focal spastic sites. Recently, it was reported that coronary microvascular dysfunction may contribute to INOCA[ 28 ], and such coronary microvascular dysfunction was more frequently observed in coronary arteries with focal spasm than in those with diffuse spasm[ 22 ]. Such coexistence of coronary microvascular dysfunction may, in part, contribute to readmission for UAP.…”
Section: Discussionmentioning
confidence: 99%
“…During the period when a PrimeWire Prestige Plus Guide Wire was available, the instantaneous free-wave ratio (iFR) was measured immediately before ACh administration in some patients. In addition, FFR was also measured in patients with coronary atherosclerosis using the conventional method of intravenous administration of adenosine triphosphate[ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…We conducted the SPT using the previously published procedures [ 11 , 12 , 13 , 14 ]. Briefly, in the SPT for the RCA, 20 and 50 µg ACh were injected into the RCA following the initial coronary angiogram (CAG).…”
Section: Methodsmentioning
confidence: 99%
“…The techniques used for the MVFT were described in a previous study [ 28 ]. The PressureWire X Cabled Guidewire (Abbot Laboratories, Abbot Park, IL, USA) was used with a pressure–temperature sensor tip.…”
Section: Methodsmentioning
confidence: 99%